Magnetism and Electromagnetism: From Theory to Application - Hussain, Dhuha Ali; Hassan, Saja Ali Abdul; Raihan, Zahraa Jamal; Mashi, Jawad Kazem Wawi; Hanon, Montadhar Zahraw (American Journal of Botany and Bioengineering, 2025)
This article presents a comprehensive study of magnetism and electromagnetism, bridging foundational theories with modern technological applications. While magnetism has been historically significant, the knowledge gap remains in its advanced integration with emerging fields like nanotechnology and spintronics. This study employs a multidisciplinary approach combining theoretical analysis, computational modeling, and case-based application review. Findings reveal that phenomena such as diamagnetism, paramagnetism, and ferromagnetism underlie critical innovations from data storage and magnetic levitation to electric motors and MRI. Results demonstrate the central role of electromagnetic theory in energy, medical, and communication technologies. The implications emphasize the necessity of continued cross-disciplinary research to optimize magnetic materials and to develop next-generation devices.